Technologies, Government Communication and Uncertainty Management in Natural Disaster Situations - Ortíz Palafox, Karla Haydeé; Valdez Zepeda, Andrés; Mora Pérez, César Omar; Lozoya Arandia , Jorge (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
Natural disasters occur and management must adjust to the reality and needs that arise. The research analyzed Technologies, Government Communication and Uncertainty Management in Disaster Cases: The Case of Landslides and Floods, particularly the role played by government communication in the disaster that occurred in the municipality of San Gabriel in the state of Jalisco, on June 2, 2019. The methodology used was a case study and also of a descriptive nature, studying the case of landslides and floods generated by an avalanche of mud, water, stones and tree trunks that invaded a large part of the municipal seat of San Gabriel, located in the south of the state of Jalisco Mexico and caused the loss of five human lives.